Renormalization group meshes and the discretization of TCAD equations. - Schoenmaker, W.
This paper presents a new method to discretize the equations for the physical modeling of semiconductor devices and back-end patterns. The method assembles planes in two dimensions and cubes in three dimensions and allows for adaptive meshing without the occurrence of spurious nodes due to mesh smoothing. Whereas the applications that are discussed focus on the design of microelectronic devices, the method is generally applicable to all fields of engineering where ab initio physical modeling is required.
Keywords: TCAD equation; Adaptive meshing; Back-end pattern; Cube assembling method; Discretization; Mesh smoothing; Microelectronic device design; Physical model; Renormalization group mesh; Semiconductor device